Evolutionary History of the Globin Gene Family in Annelids. (29th June 2020) - Belato, Flávia A; Coates, Christopher J; Halanych, Kenneth M; Weber, Roy E; Costa-Paiva, Elisa M
Abstract: Animals depend on the sequential oxidation of organic molecules to survive; thus, oxygen-carrying/transporting proteins play a fundamental role in aerobic metabolism. Globins are the most common and widespread group of respiratory proteins. They can be divided into three types: circulating intracellular, noncirculating intracellular, and extracellular, all of which have been reported in annelids. The diversity of oxygen transport proteins has been underestimated across metazoans. We probed 250 annelid transcriptomes in search of globin diversity in order to elucidate the evolutionary history of this gene family within this phylum. We report two new globin types in annelids, namely androglobins and cytoglobins. Although cytoglobins and myoglobins from vertebrates and from invertebrates are referred to by the same name, our data show they are not genuine orthologs. Our phylogenetic analyses show that extracellular globins from annelids are more closely related to extracellular globins from other metazoans than to the intracellular globins of annelids. Broadly, our findings indicate that multiple gene duplication and neo-functionalization events shaped the evolutionary history of the globin family.